Disturbi cervicali in un gruppo maschile di lavoratori non esposti a rischi ergonomici fisici / Cervical disorders in a group of male workers not exposed to physical ergonomic risks - Marchì, T.; Magarotto, G. (La Medicina del Lavoro, 2009)
L’obiettivo dello studio è di misurare la prevalenza della cervicalgia recidivante nella popolazione attiva non esposta a rischi ergonomici. Sono stati reclutati 373 lavoratori di sesso maschile occupati nel territorio veneziano. L’analisi multivariata suggerisce l’associazione dei disturbi dolorosi cervicali con algie in altri distretti articolari. Viene evidenziato un maggior livello di rischio tra i soggetti sottoposti ad alto stress lavorativo. Il rilievo di un’associazione negativa tra disturbi, anzianità lavorativa nella mansione ed esercizio di mansioni operaie conferma l’assenza di rischi ergonomici di tipo fisico nel gruppo esaminato. I risultati indicano che la quantificazione della cervicalgia, per la sua rilevanza numerica e per la breve latenza, si presta bene a valutazioni epidemiologiche con modelli di studio trasversale.Cervical disorders in a group of male workers not exposed to physical ergonomic riskObjectives: The aim of our study was to assess the prevalence of neck pain in the working population not exposed to ergonomic risks. Methods: A total of 373 male workers were recruited in the Venice area of Italy. The inclusion criterion was the absence of exposure to ergonomic risk factors at the workplace. We collected the data via interviews between March 2004 and December 2006 conducted by properly trained operators. The prevalence of neck pain episodes was calculated after selecting 347 subjects without functional outcomes for severe trauma or genetic and degenerative diseases involving the same anatomical area. The strength of the association of neck pain with the collected variables was tested by means of logistic regression analysis. Results: The group had a good attitude to doing physical activity in their free time. Exposure to high stress at work involved 12% of the sample. Multivariate analysis suggested a more than 3-fold level of risk  among individuals with high levels of stress at work. The O.R. was 3.51 for those suffering from back pain at the same time and 6.85 for those who reported shoulder pain. Conclusions: Our study, in agreement with the scientific literature, showed evidence of  increased risk of neck pain in subjects exposed to stress. There was a clear association with neck pain and joint disorders of other areas of the spine and shoulder. The results showed that the quantification of painful joint disorders, considering the numerical importance and the brief latency, is well suited to models of cross sectional studies.